2009
DOI: 10.1111/j.1600-051x.2009.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and anti‐cardiolipin antibodies in Buerger disease

Abstract: Elevated anti-CL antibody levels were associated with periodontal destruction in BD patients. Periodontopathic bacteria may serve as exogenous antigens that stimulate the anti-CL antibody production through molecular mimicry between the bacterial peptides and a host plasma protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 36 publications
3
35
0
1
Order By: Relevance
“…We have previously observed that GAgP patients demonstrate elevated levels of anti-phospholipid antibodies such as anti-phosphorylcholine and β2-glycoproteindependent anti-cardiolipin (aCL), and that GAgP patients with elevated aCL also demonstrate elevated systemic markers of vascular inflammation (Schenkein et al, 2003(Schenkein et al, , 2007. The sources of such antibodies are unknown; they may be genuine autoantibodies, or they may be produced via molecular mimicry following exposure to cross-reactive periodontal bacterial pathogens (Chen et al, 2007(Chen et al, , 2009). The involvement of such antibodies in the pathogenesis of AgP is also not known.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed that GAgP patients demonstrate elevated levels of anti-phospholipid antibodies such as anti-phosphorylcholine and β2-glycoproteindependent anti-cardiolipin (aCL), and that GAgP patients with elevated aCL also demonstrate elevated systemic markers of vascular inflammation (Schenkein et al, 2003(Schenkein et al, , 2007. The sources of such antibodies are unknown; they may be genuine autoantibodies, or they may be produced via molecular mimicry following exposure to cross-reactive periodontal bacterial pathogens (Chen et al, 2007(Chen et al, , 2009). The involvement of such antibodies in the pathogenesis of AgP is also not known.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that molecular mimicry between TLRVYK peptides on β2GPI and periodontopathic bacteria was also associated with Buerger's disease [35].…”
Section: Molecular Mimicrymentioning
confidence: 99%
“…They therefore argue that A. actinomycetemcomitans induces antibodies that mimic β2GPI. Additionally, this group has demonstrated a strong association between α-CL and periodontitis in individuals with the thrombotic Buerger's disease (Chen et al, 2009).…”
Section: Anti-cardiolipin (α-Cl)mentioning
confidence: 99%